From junk to master regulators of invasion: lncRNA functions in migration, EMT and metastasis - Dhamija, Sonam; Diederichs, Sven (International journal of cancer, 2016)
Metastasis is a multistep process that involves the dissemination of cells from the primary tumor and colonization of distant secondary organs. Epithelial cells at the invasive front of a carcinoma acquire an enhanced migratory phenotype in a process called epithelial-to-mesenchymal transition (EMT). This cellular plasticity seems to drive the initiation of metastasis. Identifying important molecules and understanding their molecular mechanisms is a key to cancer prognosis and the development of therapeutics for late stage malignancies. Recent advances in sequencing technology uncovered that the mammalian genome is pervasively transcribed into many nonprotein-coding RNAs including the class of long noncoding RNA, a.k.a. lncRNA. Several lncRNAs are differentially expressed in carcinomas and they are emerging as potent regulators of tumor progression and metastasis. Here, we review the diverse molecular mechanisms, cellular roles and regulatory patterns that are becoming apparent for the noncoding transcriptome. Chromatin modification, epigenetic regulation, alternative splicing and translational control by MALAT1, HOTAIR and TRE lncRNAs represent important examples of lncRNA-mediated control of cell migration and invasion, EMT and metastasis. Beyond these better characterized examples, numerous additional transcripts have been associated with cancer metastasis, but their functional roles await their discovery.
Gesehen am 07.05.2020